ANALISIS PENGARUH KECERDASAN INTRAPERSONAL TERHADAP HASIL BELAJAR MATEMATIKA SISWA SEKOLAH DASAR - Rosidin, Luthfia; Sarifah, Iva; Yudha, Chrisnadji (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This article discusses the analysis of the influence of intrapersonal intelligence on elementary school students' mathematics learning outcomes. There are still many students who are not aware of the potential of their intelligence, especially intrapersonal intelligence and students who are aware of the existence of their intrapersonal intelligence are still not able to utilize it optimally. It is important for students who have intrapersonal intelligence to develop an understanding of themselves, including recognizing strengths and weaknesses, controlling attitudes, managing emotions, and maintaining discipline in solving the problems they face. This research aims to conduct an intrapersonal intelligence analysis of mathematics learning outcomes, especially at elementary school level. This research uses a literature study or literature review research method using the keywords the influence of intrapersonal intelligence on elementary school students' mathematics learning outcomes. This research uses literature searches through indexed electronic media such as Google Scholar. From the search surfing process, the researcher found 5 articles that were related to the title being studied. The results of the analysis of several literature studies by researchers found that there is an influence between intrapersonal intelligence on the mathematics learning outcomes of elementary school students. It can be seen that intrapersonal intelligence has a positive and significant effect on mathematics learning outcomes.